STANISLAVSKI: LIFE IN ART - FIRST SCENES (Editora Impacto Científico, 2025)
The article investigates Konstantin Stanislavski's first artistic experiences, looking at his training as an actor and director based on family, school and amateur experiences that anticipate key aspects of his acting system. By contextualizing his career in the cultural scenario of 19th century Russia, marked by profound social and aesthetic transformations, the text shows how the impulse for a truer representation on stage is linked to the emergence of a new modern subjectivity. Along the way, it analyzes how Stanislavski transforms intuitive practices into a structured method, centered on physical action, scenic truth and the actor's creative engagement.